A coding IRAK2 protein variant compromises Toll-like receptor (TLR) signaling and is associated with colorectal cancer survival. - BOWIE, ANDREW (My University, 2014)
Within innate immune signaling pathways, interleukin-1 receptor-associated kinases (IRAKs) fulfill key roles downstream of multiple Toll-like receptors and the interleukin-1 receptor. Although human IRAK4 deficiency was shown to lead to severe immunodeficiency in response to pyogenic bacterial infection during childhood, little is known about the role of human IRAK2. We here identified a non-synonymous IRAK2 variant, rs35060588 (coding R214G), as hypofunctional in terms of NF-κB signaling and Toll-like receptor-mediated cytokine induction. This was due to reduced ubiquitination of TRAF6, a key step in signal transduction. IRAK2 rs35060588 occurs in 3-9% of individuals in different ethnic groups, and our studies suggested a genetic association of rs35060588 with colorectal cancer survival. This for the first time implicates human IRAK2 in a human disease and highlights the R214G IRAK2 variant as a potential novel and broadly applicable biomarker for disease or as a therapeutic intervention point.
PUBLISHED
Keywords: Colorectal Cancer; Toll-like receptors